2019
DOI: 10.1159/000499065
|View full text |Cite
|
Sign up to set email alerts
|

Current Treatment Patterns of Aplastic Anemia in China: A Prospective Cohort Registry Study

Abstract: Aplastic anemia (AA) is a hematologic disease characterized by pancytopenia and hypocellular bone marrow, potentially leading to chronic anemia, hemorrhage, and infection. The China Aplastic Anemia Committee and British Committee for Standards in Haematology guidelines recommend hematopoietic stem-cell transplantation (HSCT) or immunosuppressive therapy (IST) comprising antithymocyte globulin (ATG) with cyclosporine (CsA) as initial treatment for AA patients. With limited epidemiological data on the clinical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 16 publications
4
25
0
Order By: Relevance
“…Ceftazidimeavibactam (CAZ-AVI) is a novel synthetic β-lactamase inhibitor combination for a range of MDR Gramnegative infection [15,16], which was approved by the FDA in 2017. CAZ-AVI has been successfully used in patients with limited treatment options for complicated intra-abdominal infections and hospitalacquired, ventilator-associated pneumonia caused by CRE and other multidrug Gram-negative bacteria [17][18][19]. In the present study, the patient showed gradual improvement after treatment with CAZ-AVI and fosfomycin.…”
Section: Discussionsupporting
confidence: 48%
“…Ceftazidimeavibactam (CAZ-AVI) is a novel synthetic β-lactamase inhibitor combination for a range of MDR Gramnegative infection [15,16], which was approved by the FDA in 2017. CAZ-AVI has been successfully used in patients with limited treatment options for complicated intra-abdominal infections and hospitalacquired, ventilator-associated pneumonia caused by CRE and other multidrug Gram-negative bacteria [17][18][19]. In the present study, the patient showed gradual improvement after treatment with CAZ-AVI and fosfomycin.…”
Section: Discussionsupporting
confidence: 48%
“…Although CsA has achieved 40~50% of response rate and has long-term effect maintainance and survival for patients with non-severe aplastic anemia [2,3], there is still an unmet need when patients do not response, or relapse, or intolerant to CsA [8,14]. Although intensive immunosuppressive therapy with ATG, or even HSCT can further improve the response rate, these treatments are relatively expensive, risky, sometimes unavailable, and not suitable to old and weak patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the combination of ATG and CSA is superior to CSA alone for patients with NSAA [2], but in the real world, patients with NSAA were often treated with CsA alone due to the high costs and potential risks of ATG, especially in the developing counties. However, some patients do not response to CsA or relapse at the later stage of follow-up [3,4]. On the other hand, patients may also withdraw from CsA due to some severe side effects, especially kidney impairment.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of registries focused on AA in particular is reflected in the increasing number of publications describing national outcome data in AA. 2,[12][13][14] In this edition of Haematologica, Rogers et al have made an important contribution to this data pool, informing optimal diagnostic and therapeutic approaches and, equally importantly, highlighting opportunities for further research and discussion in pediatric AA.…”
mentioning
confidence: 99%